PERSEPSI DOSEN AKUNTANSI TERHADAP PRAKTIK KECURANGAN AKADEMIK PADA UPN “VETERAN” JAWA TIMUR (STUDI PADA PROGDI AKUNTANSI) - Invony Dwi Aprilisanda; Indrawati Yuhertiana; Hero Priono (Behavioral Accounting Journal, 2018)
This study aims to explore the perceptions of accounting lecturers on academic fraud in terms of the theory of moral development and the professional code of ethics of lecturers. This study uses qualitative methods with an interpretive approach, using interviews and observation as data collection techniques. The accounting lecturer for ethics courses was chosen as a resource person to obtain his opinions regarding moral values and academic fraudulent activities in the university environment. The findings of this study indicate that the perceptions of accounting lecturers are aligned with the theory of moral development and the professional code of ethics of lecturers, but the problems of the campus internal system are the main problem in fixing cultural culture of deviant behavior. In conclusion, the balance of soft skill and hard skills education must be grown with religious teachings and character by educators.